MORPHOLOGICAL FEATURES OF BRONCHOPULMONARY SYSTEM OF PATIENTS WITH PULMONARY TUBERCULOSIS - E. V. Pavlova (Креативная хирургия и онкология, 2017)
Among 113 patients operated on at the RPTD of pulmonary tuberculosis, bronchial condition has been  studied in a prospective point  of intersection, compared visual and  morphological  picture.  As a result patients were divided into 2 groups:  1st found non-specific bronchitis, endoscopically and histologically confirmed 44 patiens (38,9%), 2nd endoscopically and histologically bronchitis  is not detected 69 (61,1%) patients. Found that  is necessary to make rapid biopsy patients with ongoing bacterial  in the preoperative period in the intended place of intersection of the bronchus, even if the visual signs of inflammation of the bronchial  mucous  membrane is not detected as well as perform FBS in the near future before the operation. It’s required to do PBS control after treatment of inflammatory changes in the LDP.